Floristic composition of the Montane Forest in the Almadina-Barro Preto axis, Southern Bahia, Brazil - Coelho, Macielle Macedo; Amorim, André Márcio (Biota Neotropica, 2014)
The aim of this study is to survey the angiosperms of two montane forest remnants in the southern Bahia, Brazil: Corcovado (SCO) and Pedra Lascada (SPL). Both fragments are located in the municipality of Almadina and Barro Preto, respectively, and are 18 km distant from each other. We sampled 899 species of angiosperms distributed in 437 genera and 116 families. The SCO was the richest area with 678 species, distributed in 367 genera and 100 families. SPL showed 466 species in 269 genera and 88 families. The percentage of species identified was 85.8% and of this total, 37.7% are endemic to the Atlantic Forest, 11.2% are endemic to southern Bahia and northern Espírito Santo and 7% are disjunct between the Atlantic Forest and Amazon. The remaining percentages (44.3%) were of species widely distributed. The richest families in the two areas were Orchidaceae (10%), Rubiaceae (7%), Bromeliaceae (5.5%), Melastomataceae (4.2%) and Poaceae (4%). The richest genera were Psychotria (2%),Piper (1.8%), Ocotea (1.6%),Vriesea (1.5%) and Peperomia (1.4%). More than half of the recorded species showed non-arboreal habit, regarding life forms documented. That comes against the assertion that many authors in the tropical forests, where species richness in angiosperms is expected for non-woody species, especially in montane forests. Twelve species have been identified as new, but seven others already described from collections previously obtained in these two areas. Orchidaceae, Rubiaceae, Poaceae and Bromeliaceae showed significant richness in this study these families are commonly reported as the richest in other inventories in the Atlantic Forest in southern Bahia reinforcing their importance to the regional flora. The high levels of richness, endemism, and the growing numbers of new taxonomic discoveries from the SPL and SCO sites indicate the biological importance of these two forest remnants. The implementation of parks or other protected environmental reserves would be essential to the conservation of its species.